Playing evolution in the laboratory: From the first major evolutionary transition to global warming - De mendonça fragata almeida, Inês (2020)
Experimental evolution allows testing hypothesis derived from theory or from observed patterns in nature. We have designed a droplet-based microfluidic ‘evolution machine’ to test how transient compartmentalization (‘trait-groups’) of independent molecular replicators (likely a critical step in the origin of life) could have prevented the spread of parasitic mutants; that is, inactive RNAs that have been reported to spoil a system of free replicators. In remarkable agreement with the theory, we show that this simple population structure was sufficient to prevent takeover by inactive RNAs. A more complex scenario arises when we use experimental evolution to test field-derived hypothesis; for instance, the idea that temperature is driving genetic spatiotemporal patterns of climate change. In the fly Drosophila subobscura, latitudinal clines in gene arrangement frequencies occur worldwide, and more equatorial gene arrangements are becoming more frequent at higher latitudes as a correlated response to climate change. However, the evolution at different constant temperatures in the laboratory was not consistent with patterns in nature, suggesting some limitations of experimental evolution. Finally, also in D. subobscura, we show that repeatability in experimental evolution is staggeringly consistent for life history traits, making evolution quite predictable and suggesting that laboratory selection can quickly erase differences between populations. Yet, the genetic paths used to attain the same adaptive phenotypes are complex and unpredictable.